A Research on the Factors Affecting the Negative Attitudes of Turkish Banking Sector Customers towards Branchless Digital Banking - Mustafa Beybur (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
The rapid digitalization in the banking sector has revealed the branchless digital banking approach, unlike the traditional banking approach, where branches are used extensively as distribution channels. The customer portfolios reached by the new generation branchless digital banks attract great notice. This new banking approach also attracted the attention of the Turkish banking sector and branchless digital banking activities were made possible with the regulations prepared by the BRSA. Branchless digital banking is a new field of activity in Turkish banking sector and it is accepted that on the adoption of an innovation by the users the intention towards the innovation is effective, and on the intention towards the innovation the attitude towards the innovation is effective. It is stated that many external factors are effective on the attitude towards innovation. Therefore, in this research, it has aims to investigate some factors that affect on the negative attitudes of bank customers towards branchless digital banking. For this purpose, an online questionnaire was applied to 357 traditional bank customers and the answers were subjected to regression analysis. With the regression analysis, the effects of trust, perceived usefulness, traditional bank usage habits and satisfaction factors on branchless digital banking on the negative attitude towards branchless digital banking were analyzed. The results show that the negative attitude towards branchless digital banking was significantly and positively affected by traditional bank usage habits, trust towards branchless digital banking and perceived benefit towards branchless digital banking, but not significantly affected by traditional bank satisfaction.